2012
DOI: 10.1155/2012/148039
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of the Vitreous Humour

Abstract: The human vitreous humour (VH) is a transparent, highly hydrated gel, which occupies the posterior segment of the eye between the lens and the retina. Physiological and pathological conditions of the retina are reflected in the protein composition of the VH, which can be sampled as part of routine surgical procedures. Historically, many studies have investigated levels of individual proteins in VH from healthy and diseased eyes. In the last decade, proteomics analyses have been performed to characterise the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 49 publications
1
67
0
3
Order By: Relevance
“…Rhegmatogenous RD occurs when the tractional forces of the vitreous on the retinal tear permit the fluid from the vitreous humor to enter the subretinal space (SRS). Vitreous fluid contains a large amount of cytokines and growth factors that stimulate the activation and the proliferation RPE and retinal glial cells [12, 18]. …”
Section: Etiopathogenesis Of Pvrmentioning
confidence: 99%
“…Rhegmatogenous RD occurs when the tractional forces of the vitreous on the retinal tear permit the fluid from the vitreous humor to enter the subretinal space (SRS). Vitreous fluid contains a large amount of cytokines and growth factors that stimulate the activation and the proliferation RPE and retinal glial cells [12, 18]. …”
Section: Etiopathogenesis Of Pvrmentioning
confidence: 99%
“…In a comparative proteomics study the protein composition of retina and vitreous humour was analysed showing proteins which functionally interact with each other to control oxidative stress, immune reactions and the exchange of intracellular proteins between the retina and vitreous [63]. It was demonstrated that the total protein content reported for the vitreous of patients with DR is higher than in the non-diabetic and control samples [64].…”
Section: Proteomic Methods Applied For Dr Diagnosismentioning
confidence: 99%
“…LL-37 cathelicidin is an α-helix type AMP of the tear fluid mainly produced by the corneal epithelial cells. Similar to the defensins, cathelicidin exerts various antimicrobial [102] and immunomodulatory functions [54] Complement C4b [64] Brain-specific angiogenesis inhibitor 1-associated protein 2 [70] Lysozyme C [38] VEGF [56] Complement C9 [64] Cystathionine b-synthase [70] Lipophilin A [38] Complement factor B [64] MMP-13 [70] Immunoglobulin lambda chain [38] Pigment epithelial-derived factor [64] Podocan [70] Hsp27 [76] Interstitial retinol-binding protein [64] Selenoprotein P [70] β 2 -Microglobulin [76] Inter-α trypsin inhibitor heavy chain [64] Enolase [77] [95]. In addition, it has an important role in re-epithelialization during wound healing [107].…”
Section: The Chemical Barrier Of the Tears As A Possible Source For Bmentioning
confidence: 99%
“…The differential expressions of angiopoietin-related protein 6, apolipoprotein A-I, estrogen receptor alpha, and tubulin were confirmed by Western blot analysis [75]. Since improved and more sensitive techniques for the proteome analysis are emerging, new data are expected [76]. …”
Section: Proteomicsmentioning
confidence: 99%